Application of the Gonadotropin-Releasing Hormone (GnRH) Useful for Induced Spawning of the Fat Snook (Centropomus parallelus Poey, 1860) - Lara, Daniel Cortez; González, Rodrigo Cuervo; Meza, Eduardo Alfredo Zarza (Newest Updates in Agriculture and Veterinary Science Vol. 3, 2023)
The present study aimed to investigate the Gonadotropin-Releasing Hormone (GnRH) useful for Induced Spawning of the Fat Snook (Centropomus parallelus Poey, 1860). The fat snook (Centropomus parallelus), a catadromous species highly valued for human consumption, is widely distributed along the American continent's Atlantic coast, from the United States to Brazil. It is common in the waters off the Gulf of Mexico's coastal states, particularly Tamaulipas, Veracruz, Tabasco, and Campeche. Because it is critical to ensure maturation and reproduction under controlled conditions, and because this is inhibited in captivity, spawning of the Centropomus parallelus was induced in the current study using a dose of gonadotropin-releasing hormone (GnRH). Advanced gonad maturity was observed, while two females in a vitellogenic state reached final maturation with the application of a 50 \(μ\)g/kg dose of the hormone and the male subjects failed to present spermiation under the application of the same dose. While maturation and spawning may be induced in both females and males recently captured in the wild, successful results require that they are acclimatized over a longer period of time, above all in terms of diet.